Implementar un sistema de gestión de seguridad y salud en el trabajo en la “clínica veterinaria mascotas”, de conformidad con el decreto 1072 del 2015 y la resolución 1111 del 2017 (2019)
The objective of this degree work is the implementation of the Occupational Health and Safety Management System in accordance with the requirements of Decree 1072 of 2015 "Single Regulatory Decree of the Labor Sector" in the Clínica Veterinaria Mascotas, this in order to minimize the risks and the dangerous ones. Initially a diagnosis is made, so it is known as the initial state of the company based on the level of compliance with the application of the system, it is met in the middle of the table of values and the qualification of the minimum levels of the resolution 1111 of 2017 Monitoring of the matrices corresponding to the system, stories such as the legal matrix, which identify the different norms, laws, resolutions and decrees that apply to the company and the subject of hazard identification and risk mitigation, with La search for risks. The formula of the improvement plan of the middle of a Gantt chart, which allows to know the programming and the execution of the activities and its time. The above generates the creation of a policy and objectives that guarantee the commitment of the company with its workers.